Concomitant stromal tumor and early cancer of the stomach: What should be done?. Issue 29 (July 2017) - Xu, Yan; Shen, Liangfang; Lu, Zhaoxia; Liu, Xiaowei; Wu, Wei; Feng, Deyun; Rao, Jaladanki N.; Xiao, Lan; Ouyang, Miao
Abstract : Abstract: Concomitant gastric stromal tumor (GST) and gastric cancer (GC) is uncommon; even more uncommon is a concomitant GST and early stage GC (EGC). Tumor resection by endoscopic submucosal dissection (ESD) for concomitant GST and EGC has not been reported. We sought to define the clinical importance of detection of concomitant GST and EGC during the first esophagogastroduodenoscopy (EGD), and compare the clinical outcomes of ESD versus radical surgery for the treatment of concomitant GST and EGC. Our investigation was a retrospective cohort study. Patients with concomitant GST and EGC who underwent ESD or radical surgery were enrolled at the university-affiliated hospital from January 2005 to January 2015. The detection rate of concomitant GST and EGC during the first EGD was 3/25 (12%). Among 25 patients, 14 underwent ESD and 11 underwent surgery. Mean operation time and hospital stay were significantly shorter in the ESD group than the surgery group. There were no significant differences in terms of rates of en bloc resection, complete resection, and early complications. Late complications were more common in the surgery group than in the ESD group. The median follow-up duration was 58.9 months. Three- or 5-year overall survival rates were 100% for both groups and no patient died of EGC and GST. There was no local recurrence in the 2 groups; however, 3 metachronous EGC lesions were found during the follow-up period in the ESD group as follows: the simultaneous occurrence of GST and EGC was uncommon; the detection rate of concomitant GST and EGC was very low at the first EGD; and ESD appeared to be a safe, efficient, and popular treatment option for concomitant GST and EGC, that met the ESD absolute indication, and the outcomes were comparable to those achieved with surgery.